New Mutation in ParE in a Pneumococcal In Vitro Mutant Resistant to Fluoroquinolones - Janoir, Claire (American Society for Microbiology, 2001)
For an in vitro mutant of Streptococcus pneumoniae selected on moxifloxacin four- to eightfold-increased MICs of new fluoroquinolones, only a twofold-increased MIC of ciprofloxacin, and a twofold-decreased MIC of novobiocin were observed. This phenotype was conferred by two mutations: Ser81Phe in GyrA and a novel undescribed His103Tyr mutation in ParE, outside the quinolone resistance-determining region, in the putative ATP-binding site of topoisomerase IV.